Conflict Resolution of Territorial Boundaries in Indonesia Through a Regulatory Approach - Nurhidayat Nurhidayat; Kusuma Kusuma; Arifuddin Uksan; Pujo Widodo; Orin Wijayanti (CV. AFDIFAL MAJU BERKAH, 2023)
The Boundaries are important in maintaining national stability and security. Conflicts over territorial boundaries are common, both between countries and between provinces and regencies/cities. This is one of the important issues that have escaped the attention of the government so that various disputes arise between the community and the political elite at the border. The conflicts that occur are more caused by the triggering factor of boundary disputes, which in general have not been resolved due to the problem of resolving boundary lines due to different perceptions of the community and political elites. Boundary conflicts are usually very vulnerable if the contested area has excellent natural and economic resource potential. The purpose of this study is to describe the factors that cause conflict and the urgency of affirming boundaries and describe resolution efforts in efforts to resolve boundaries through regulation and non-regulation. The method used is a qualitative method with a descriptive type of approach through literature study. Based on the research results, it is understood that conflict resolution is used through two channels, namely: Non-litigation settlement of boundary conflicts and litigation settlement, Non-litigation is also called conflict resolution through government administration, in this case, mediated by the Ministry of Home Affairs and the Governor. While conflict resolution by litigation through judicial review and lawsuits filed by the parties to the Supreme Court or the Constitutional Court. The role of the government in resolving regional border conflicts is as a facilitator in the context of investigating conflicted cases, as well as a mediator in negotiations in resolving boundary conflicts